Mangupa Lahiron Daganak sebagai Representasi Penghayatan Iman Kristiani Umat Suku Batak Toba - Stephanus Lisdiyanto (Sekolah Tinggi Teologi Simpson Ungaran, 2023)
In this article, the author would like to express his appreciation for the faith of the Toba Batak Catholics in the parish of St. John the Baptist, Perawang Riau, Padang Diocese, related to the Mangupa Lahiron Daganak tradition carried out in the Toba Batak tribal community. The Mangupa Lahiron Daganak tradition is one of the ceremonies to welcome and give thanks for the birth of a child in the Toba Batak family. This tradition is no longer carried out completely by Toba Batak Catholics in the parish of Saint John the Baptist Perawang Riau. Several instruments are used in the ritual of the Mangupa Lahiron Daganak ceremony. The function of this instrument is to make the ceremony run smoothly, wisely, and meaningfully. The instruments used in the ceremony contain symbols that are meaningful in people's lives. The purpose of this paper is to find and interpret the symbols in the Mangupa Lahiron Daganak ceremony, not only from a social point of view but more on theological meanings that can strengthen the appreciation of the faith of Catholics, especially the Toba Batak people. The results showed that the Toba Batak Catholics in the St. John the Baptist Perawang Riau parish were able to find social meaning, which was then transformed into an appreciation of the Christian faith, even though the Toba Batak people in the St. John the Baptist Perawang Riau parish no longer held the full Mangupa Lahiron Daganak ceremony.